Speech by the Honourable Dr. Lim Chong Eu, Chief Minister Penang at the Official Opening Ceremony of Chienese Medium School Headmasters Course (Penang) on 29th October 1976At 9.15 a.m. at Dewan Sri Pinang. - Lim, Chong Eu (1976)
From time to time Government hold Civic Courses of this nature but this particular Course is special one because your is a professional one specialising on education.